KONSEP PENGEMBANGAN DESA EKOWISATA PAMPANG BERBASIS PARTISIPASI MASYARAKAT - Susanto, Eko; Zuhri, M. Tammima; Muwuri, Kantun (KRITIS, 2012)
Community empowerment is the main driving force which can assist the development of a tourist village. The utilization of natural potential also becomes an attraction in the development of a tourist village. Ecotourism Village concept could connect the needs of community-based tourism and the need for environmental management for sustainable tourism. This article provides an overview of Pampang Ecotourism Village's development concept. Pampang Village is located in Gunung Kidul Regency, Yogyakarta Special Region. This article also presents findings regarding eco-tourism potential sources, driving factors, and inhibiting factors in the development of Pampang Eco-tourism Village.